Working capital management and managerial talent. Issue 3 (26th August 2020) - Ujah, Nacasius U.; Tarkom, Augustine; Okafor, Collins E.
Abstract : Purpose: Talented managers arguably remain quintessential to firm value and performance. While the literature offers evidence for the long-term orientation of talented managers, there is a paucity of evidence on the short-term performance of managers. Here, we examine the relationship between managerial talent and working capital management (WCM). Design/methodology/approach: This study primarily employs a panel fixed-effect method controlling for firm-year and firm-industry for non-financial and non-utility firms for the years 1980 through 2016. Also, the authors control of potential bias that may impact the result. These controls include social capital, financial constraints and tests for endogeneity and spurious correlation. Findings: The authors find the association between managerial talent and WCM to be positive and significant. The results indicate that talented managers have a higher cash conversion cycle. The empirical evidence still holds after controlling for social capital, religiosity and financial constraints. Also, the evidence still holds by employing an interaction term between Tobin's Q as a proxy for investment opportunities and talented managers. Practical implications: The finding may lend credence to executive contracts. Human nature, by default, is only vested on a net benefit for self-aggrandization. Self-aggrandization can be evident through structures in managerial contracts. These contracts usually tie consequences to long-term growths. If a benefit is offered based on short-term operational goals, talented managers may do more to the management of working capital. Originality/value: In the managerial talent literature, talents reflect a holistic picture of one that can succeed in both the short-term and long-term goals of a company. Here, the authors show that talented managers are inefficient in meeting short-term goal – working capital management. Thus, the authors add to the research by providing evidence that talented managers are myopic.